Epigenome-wide DNA methylation profiling in septic and non-septic patients with similar infections: potential use as sepsis biomarkers - López-Cruz, Ian; García-Giménez, José Luis; Madrazo, Manuel; García-Guallarte, Judit; Piles, Laura; Pallardó, Federico V.; Artero, Arturo (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionSepsis is a life-threatening condition caused by a dysregulated immune response to infection, leading to organ failure. Despite its significant global burden, the underlying mechanisms of immune dysfunction in sepsis remain incompletely understood. This study explores the role of DNA methylation in white blood cells in sepsis pathogenesis.MethodsA prospective case-control study was conducted to compare DNA methylation profiles between patients with community-acquired sepsis and matched controls who had similar infections but did not develop sepsis. Whole blood samples from these patients were analyzed using the Infinium MethylationEPIC v2.0 kit, enabling genome-wide methylation analysis. Selected genes with differential methylation were validated by pyrosequencing.ResultsSignificant differential DNA methylation patterns were identified between septic and non-septic individuals uising. Our results suggest that DNA methylation changes are closely linked to the pathophysiological processes of sepsis, influencing immune cell activation, inflammation, and organ dysfunction. The most prominent findings include the hypomethylation of immune-related genes (SERPINA1, AZU1, MPO, and SLX4), which were strongly correlated with clinical severity and inflammatory markers such as SOFA scores and PCT levels. Correlation analyses demonstrated significant associations between the methylation levels of these genes and clinical severity markers, such as SOFA score and PCT levels. Notably, SLX4 hypomethylation showed the highest predictive value for poor prognosis (AUC 0.821), while SERPINA1 hypomethylation exhibited strong diagnostic potential for sepsis (AUC 0.858).DiscussionOur results underscore the potential of DNA methylation changes, particularly in immune-related genes, to enhance the early detection of sepsis and to stratify patients based on severity. Future research should explore the therapeutic implications of these epigenetic alterations in sepsis care.